Elodeids, but not helophytes, increase community diversity and reduce trophic state: Case study with rotifer indices in field ponds - Natalia Kuczyńska-Kippen (Elsevier, 2021)
Despite the large number of ponds scattered across the landscape, there is still insufficient recognition of their functioning. This would require the development of methods for assessing this type of aquatic ecosystem, based on their environmental specificity. Even though conditions are potentially homogenic in small and shallow water bodies, macrophytes divide the area into diverse microhabitats. Therefore, we hypothesized that the type of habitat (the open water vs. various macrophytes) may have a considerable structuring effect on functional groups, such as life-forms (pelagic and littoral) or trophic-associated rotifers, confirming their great suitability for environmental studies. Sixty three ponds, with 136 sites located within the open water, helophytes and elodeids, were analysed. Eutrophic rotifers showed a similar response to environmental factors and were linked to a certain type of habitat as was the whole pelagic community, while mesotrophic rotifers, which ecologically also belong to the pelagic community, responded in the same way as the littoral community and species diversity. The first group of rotifer indices, pelagic rotifers and their eutrophic fraction prevailed in the open water of fishstock large-surfaced ponds. However, the second group consisting of littoral rotifers along with overall species diversity and mesotrophic fraction, increased concurrently with the presence of crustaceans in small-surfaced ponds overshaded by nymphaeids and pleustophytes. The presence of elodeids in ponds, particularly Ceratophyllum and Chara, with the highest complexity (plant biomass), apart from increasing the diversity and share of littoral rotifers, reduced the occurrence of eutrophic rotifers and increased that of mesotrophic ones. This confirms the viability of using certain trophic indicators for water quality prediction in ponds. While elodeids were of the greatest importance, helophytes did not impact rotifer distribution, having no indicative value for quality state assessment in ponds. We demonstrate that a functional approach, taking into account rotifer life forms (pelagic vs. littoral community), may serve as a valuable tool for environmental analyses in case of small water bodies. Rotifer indices revealed not only a prevalence towards a particular type of habitat but they also selectively chose certain species of macrophyte beds, which suggests that for conservation purposes a highly complex cover of elodeids should be maintained to improve the ecological value of ponds.